Research of wearproofness of pair of friction in the environment of cornmeal with additions of mineral saponite - Каплун, В.Г.; Гончар, В.А. (Problems of Tribology, 2014)
In the article the results of experimental tests of patterns made from the different brands of steel and technologies of treatment of surfaces in the model environment of cornmeal with additions of mineral of saponite are presented.